Universiti Utara to expand business - The, Sun (The Sun, 2012)
SINTOK : Uniutama Management Holdings Sdn Bhd (UMHSB), a wholly-owned subsidiary of Universiti Utara Malaysia (UUM), plans to go into business in a big way.